Pengaruh Daya Tarik Iklan, Kualitas Produk, Citra Merek, Serta Harga Terhadap Keputusan Pembelian Luwak White Coffee Di Toko Virdasari Desa Sitanggal Kabupaten Brebes - Siti Marselia; Aisyah Nur Rismayanti; Khalid Iskandar; Indah Dewi Mulyani; Nur Afridah (Universitas 17 Agustus 1945 Semarang, 2023)
One of the new beverage or food industry competitions that are ready to compete and enter the market nationally is the white coffee industry. Efforts to increase promotion, price adjustments, and product quality, or need to carry out a more effective marketing strategy in accordance with the findings of market research conducted. The purpose of this study is to analyze the influence of advertising attractiveness, product quality, brand image, and price on purchasing decisions for Luwak White Coffee drinks. The quantitative approach method carried out is based on concrete research data, which is a numerical value that will be measured by statistics as a calculation test tool and related to problems, resulting in a conclusion. The population of this study was consumers of Luwak White Coffee drinks at the Virdasari store in SiDate Village. The sample was obtained from subjects 25% of the population of 332 people, obtained 83 respondents. The research instrument used is the primary data from filling out the questionnaire. The results of the study found that advertising attractiveness does not affect purchasing decisions, product quality does not affect purchasing decisions, brand image does not affect purchasing decisions, price affects purchasing decisions. Simultaneously, advertising attractiveness, product quality, brand image and price influence purchasing decisions at Toko Virdasari Desa SiDate